EFFECTS OF DIGITAL MARKETING ON BUYING BEHAVIOR AMONG THE ONLINE BUYERS IN CHIDAMBARAM - Narayanan, T. B. Badhri (International Journal of Research -GRANTHAALAYAH, 2021)
In this context, digital marketing is the best possible way to meet out the objectives. It is the usage of techniques for reaching a larger audience through some channels like the websites, social media, online advertisements through search engines, advertisements made through multimedia, interactive marketing, e-marketing, mobile marketing and so on. The current research study aims to explore the influence of such digital marketing on the buying behavior of consumers. This study has used questionnaires for the purpose of data collection from the respondents of Chidambaram who made online purchase. the respondents are selected on the basis of simple random sampling and the sample size of the study is 100. The data collected for the study is put into regression analysis for further interpretation of the data. The study reveals the finding that the digital marketing has got a positive influence over the buying behavior.